Bundling in banking - strategy to increase profits - Koderisch, Martin (Henry Stewart Talks, 2008)
Current use of bundling in retail, private and commercial banking, Best practices in bundling, Learning from other industries, Importance of a structured and scientific approach to bundling, Overview of the theory of consumer surplus, Step process framework, How to create successful bundles in financial services